Differences in hindlimb morphology of ducks and chickens: effects of domestication and selection. Issue 1 (December 2015) - Duggan, Brendan; Hocking, Paul; Schwarz, Tobias; Clements, Dylan
Abstract Background Poultry account for the most numerous species farmed for meat and have been subject to intense selection over approximately 60 generations. To assess morphological changes which have occurred in the avian leg due to selection for rapid growth and high meat yields, divergent lines of chicken (Gallus gallus ) and duck (Anas platyrhynchos ) were studied between 3 and 7 weeks of age. For each line, femoral and tibiotarsal morphology was recorded using computed tomography scanning and tibiotarsal bone quality measures (stiffness, bending stress and porosity) were assessed. Results In chicken and duck, divergence in hindlimb morphology has occurred in the commercial meat lines compared to their lighter conspecifics. As expected, the differences were largest between species. Leg development nears completion much earlier in ducks than in chickens. Duck tibiotarsi showed a large degree of lateral curvature, which is expected to affect foot position during swimming and walking, and thus to influence gait. All lines have adapted their tibiotarsal morphology to suit the loading forces they experience; however bone quality was found to be poorer in chickens. Conclusions We demonstrate that intensive selection for growth rate in both chickens and ducks has resulted in leg morphology changes, which are likely to influence gait. Ducks represent an interesting compromise of adaptation for efficient locomotion in two media—on land and in water. Some aspects of bone morphology in the duck, such as lateral curvature of the tibiotarsus, may result from adaptation to swimming, which potentially imposes limitations on terrestrial locomotion.